Dystonia - Different Prospects 2018
DOI: 10.5772/intechopen.78760
|View full text |Cite
|
Sign up to set email alerts
|

Tardive Dystonia due to D2 Antagonists and Other Agents

Abstract: Tardive dystonia due to D2 antagonists or other agents is a potentially severe extrapyramidal side effect emerging after long-term drug treatment, prevalent but not limited to psychiatric populations. Its course is often deteriorating, and available treatments are frequently far from satisfying. It presents with sustained muscle contractions, abnormal postures, and repetitive twisting movements and leads to increased psychiatric morbidity, mortality, and decline of quality of life. Inadequate clinical skill an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…These effects are more pronounced with tardive dystonia cases and can even lead to social avoidance, isolation, and stigmatization. 59 Hence, both non-motor and motor features associated with dystonia should be managed in order to improve the quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…These effects are more pronounced with tardive dystonia cases and can even lead to social avoidance, isolation, and stigmatization. 59 Hence, both non-motor and motor features associated with dystonia should be managed in order to improve the quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…22 Multiple review papers have commented on the impure and heterogenous nature of tardive syndromes previously. [23][24][25] Additionally, a 1999 study of 100 individuals with TD showed 35% had two or more of the following TS: CTD; tardive tremor; tardive akathisia; tardive dystonia; tardive tics, and myoclonus. 26 However only 16% had tardive dystonia and 4% had tardive tics.…”
Section: Discussionmentioning
confidence: 99%
“…A single‐blind randomised trial involved 45 patients, which compared quetiapine and haloperidol for treating CTD showed favourable results for quetiapine 22 . Multiple review papers have commented on the impure and heterogenous nature of tardive syndromes previously 23–25 . Additionally, a 1999 study of 100 individuals with TD showed 35% had two or more of the following TS: CTD; tardive tremor; tardive akathisia; tardive dystonia; tardive tics, and myoclonus 26 .…”
Section: Discussionmentioning
confidence: 99%
“…1 TD is a well-recognized subtype of tardive dyskinesia, characterized by slow involuntary sustained twisting movements often painful, affecting face, neck, limbs, or trunk. [1][2][3] We report a patient with severe axial tardive dystonia after psychotropic polypharmacy who responded to clozapine optimization.…”
mentioning
confidence: 99%
“…In our patient, olanzapine and amisulpride could be incriminated for precipitating TD because the chances of having TD with clozapine or quetiapine exposure is extremely rare due to their low D2 affinity and fast dissociation property. 3…”
mentioning
confidence: 99%